2008
DOI: 10.1111/j.1708-8305.2008.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Infection Among International Travelers Globally

Abstract: This analysis of morbidity associated with oral ingestion of pathogens abroad determines which parts of the world currently are high-risk destinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
4
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 21 publications
5
69
4
8
Order By: Relevance
“…Travel destination was found previously to be the most influential risk factor for travel-associated diarrhea. 21,22 In agreement with our data, destinations in North Africa in particular were described previously to be associated with increased risk for travel-related diarrhea. 9,20 Although ill children returning from other world regions considered to be high-risk areas for travel-associated diarrhea (ie, southern Asia and sub-Saharan Africa) 22 showed evidence of significant risk of disease, no significant proportionate increase was noted, compared with children returning from Europe or North America.…”
Section: Figuresupporting
confidence: 82%
“…Travel destination was found previously to be the most influential risk factor for travel-associated diarrhea. 21,22 In agreement with our data, destinations in North Africa in particular were described previously to be associated with increased risk for travel-related diarrhea. 9,20 Although ill children returning from other world regions considered to be high-risk areas for travel-associated diarrhea (ie, southern Asia and sub-Saharan Africa) 22 showed evidence of significant risk of disease, no significant proportionate increase was noted, compared with children returning from Europe or North America.…”
Section: Figuresupporting
confidence: 82%
“…The high overall incidence in Turkey was attributed to gastroenteritis, whereas the next highest figures in Greece and Spain were mainly due to respiratory tract infections. Greenwood et al described a low risk of gastroenteritis for southern Europe [27], yet we found an elevated incidence in Greece and Spain.…”
Section: Findings On Incidence Of Illness and Injurycontrasting
confidence: 46%
“…As data have been unrelated to numbers of travellers per site, the main point of criticism has been that proportions of health problems easily suffer distortion [20]. Some reports have described single imported diseases in relation to national travel statistics [25] or World Tourism Organization data [26,27], but a thorough overview of travellers' health risks has been lacking.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Contrary to the widely held belief that travelers to South Africa are at low risk of acquiring traveler's diarrhea, 5,6 our data show that South Africa travelers are just as likely to present with traveler's diarrhea as those from neighboring countries in the region. Acute, unspecified diarrhea was the most common category reported, which may reflect the practice of an empiric trial of treatment with antibiotics before detailed diagnostic studies.…”
contrasting
confidence: 52%